Optimized self-microemulsifying drug delivery system improves the oral bioavailability and brain delivery of coenzyme Q10 - Thapa Chhitij; Jo-Eun Seo; Taekwang Keum; Gyubin Noh; Santosh Bashyal; Shrawani Lamichhane; Jung Hwan Kim; Jae Heon Lee; Jee Hun Park; Jaewoong Choi; Se Hyun Song; Sangkil Lee (Taylor & Francis Group, 2022)
Our study aimed to develop a self-microemulsifying drug delivery system for the poorly aqueous-soluble drug Coenzyme Q10, to improve the dissolution and the oral bioavailability. Excipients were selected based on their Coenzyme Q10 solubility, and their concentrations were set for the optimization of the microemulsion by using a D-optimal mixture design to achieve a minimum droplet size and a maximum solubility of Coenzyme Q10 within 15 min. The optimized formulation was composed of an oil (omega-3; 38.55%), a co-surfactant (Lauroglycol® 90; 31.42%), and a surfactant (Gelucire® 44/14; 30%) and exhibited a mean droplet size of 237.6 ± 5.8 nm and a drug solubilization (at 15 min) of 16 ± 2.48%. The drug dissolution of the optimized formulation conducted over 8 h in phosphate buffer medium (pH 6.8) was significantly higher when compared to that of the Coenzyme Q10 suspension. A pharmacokinetic study in rats revealed a 4.5-fold and a 4.1-fold increase in the area under curve and the peak plasma concentration values generated by the optimized formulation respectively, as compared to the Coenzyme Q10 suspension. A Coenzyme Q10 brain distribution study revealed a higher Coenzyme Q10 distribution in the brains of rats treated with the optimized formulation than the Coenzyme Q10 suspension. Coenzyme Q10-loaded self microemulsifying drug delivery system was successfully formulated and optimized by a response surface methodology based on a D-optimal mixture design and could be used as a delivery vehicle for the enhancement of the oral bioavailability and brain distribution of poorly soluble drugs such as Coenzyme Q10.